Deciphering the conserved genetic loci implicated in plant disease control through comparative genomics of Bacillus amyloliquefaciens subsp. plantarum - Hossain, Mohammad J.; Ran, Chao; Liu, Ke; Ryu, Choong-Min; Rasmussen-Ivey, Cody R.; Williams, Malachi A.; Hassan, Mohammad K.; Choi, Soo-Keun; Jeong, Haeyoung; Newman, Molli; Kloepper, Joseph W.; Liles, Mark R. (Frontiers in Plant Science, 2015)
To understand the growth-promoting and disease-inhibiting activities of plant growth-promoting rhizobacteria (PGPR) strains, the genomes of 12 Bacillus subtilis group strains with PGPR activity were sequenced and analyzed. These B. subtilis strains exhibited high genomic diversity, whereas the genomes of B. amyloliquefaciens strains (a member of the B. subtilis group) are highly conserved. A pairwise BLASTp matrix revealed that gene family similarity among Bacillus genomes ranges from 32- 90%, with 2,839 genes within the core genome of B. amyloliquefaciens subsp. plantarum. Comparative genomic analyses of B. amyloliquefaciens strains identified genes that are linked with biological control and colonization of roots and/or leaves, including 73 genes uniquely associated with subsp. plantarum strains that have predicted functions related to signaling, transportation, secondary metabolite production, and carbon source utilization. Although B. amyloliquefaciens subsp. plantarum strains contain gene clusters that encode many different secondary metabolites, only polyketide biosynthetic clusters that encode difficidin and macrolactin are conserved within this subspecies. To evaluate their role in plant pathogen biocontrol, genes involved in secondary metabolite biosynthesis were deleted in B. amyloliquefaciens subsp. plantarum strain, revealing that difficidin expression is critical in reducing the severity of disease, caused by Xanthomonas axonopodis pv. vesicatoria in tomato plants. This study defines genomic features of PGPR strains and links them with biocontrol activity and with host colonization.